The Effect of PowerPoint Presentation Based on the Students' Score in Grammatical Competence to the Eleventh Grade Students of SMA Negeri 1 Simo - Pratiwi, Wenny; , Nur Hidayat, M.Pd (2017)
There are two purposes in this research. The first is to know whether any significant difference on the students‟ score of eleventh grade students of SMA Negeri 1 Simo who are taught grammar using PowerPoint presentation and white board or not. Then, the second purpose is to know how significant is the effect of PowerPoint presentation and white board in teaching grammar on the students' score of eleventh grade students of SMA Negeri 1 Simo. The type of this research is quantitative research. The design of the research is quasi-experiment. The research population is 265 students of Eleventh grade in SMA Negeri 1 Simo. The sample of the research are XI IPA 1 as the experiment class and X1 IPA 2 as the control class. The researcher used cluster random sampling to determine the sample. Then the methods of collecting data are test and documentation. To analyse the data, the researcher used one way analysis of variance with 5% significance level. The result of the research is there is no significant difference on the students‟ score of eleventh grade students of SMA Negeri 1 Simo who are taught grammar using PowerPoint presentation and white board. Then, the insignificant difference of the effect of PowerPoint presentation and white board in teaching grammar on the students‟ score of eleventh grade students of SMA Negeri 1 Simo is showed by the result of one way ANOVA test. The test showed that the difference both of media is 1.23.